Signified Deviations in Federer’s What Every American Needs to Know About the Qur’an: A Saussurean Analysis of Islamic Themes - Sugandi, Fatima Aurelian; Ubaidillah, Ubaidillah; Gafarov, Anar (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Western orientalist writings on Islam often present selective historical narratives that influence public understanding of Islamic teachings. One of these works is William J. Federer’s What Every American Needs to Know about the Qur’an – A History of Islam and the United States, which portrays Islam, the Qur’an, and the Prophet Muhammad in ways that raise theological and textual concerns. This study aims to analyze how key signifiers, Islam, the Qur’an, and the Prophet Muhammad are associated with signified meanings that deviate from established Islamic interpretations. Using Ferdinand de Saussure’s semiotic framework and a qualitative descriptive method, this research identifies three major patterns of signified deviation: (1) Islam is linked to coercion and revenge despite Qur’anic principles of religious freedom and forgiveness; (2) the Qur’an is portrayed as legitimizing violence and sexual misconduct through selective readings of specific verses; and (3) the Prophet Muhammad is represented as acting based on personal desire rather than divine command. The study concludes that these deviations result from reassigning signified meanings to key Islamic signifiers, producing an ideologically framed interpretation. This research contributes to understanding how semiotic processes shape contemporary representations of Islam in orientalist discourse.